Fasciola hepatica Diagnosis: Clinical and Laboratory Clues from A University Hospital Experience - Sağmak Tartar, Ayşe; Aşan, Mehmet Ali; Bozdağ, Ahmet; Bahçecioğlu, İbrahim Halil; Akbulut, Ayhan; Demirdağ, Kutbeddin (Galenos Publishing House, 2025)
Objective: Fascioliasis is a trematode infection caused by Fasciola hepatica or Fasciola gigantica. Diagnosis of fascioliasis is often delayed. This study aims to contribute to reducing the incidence of the disease by determining regional epidemiology and guiding public health measures, as well as increasing awareness among physicians through the examination of clinical, laboratory, and imaging findings. Methods: Patients diagnosed with fascioliasis at the Infectious Diseases Clinic and Gastroenterology Clinic of Fırat University Hospital between 2011 and 2022 were included in the study. Demographic information, clinical findings, complete blood count, biochemical parameters, radiological imaging reports, treatment, and prognosis were examined. Patient data were obtained from the hospital automation system, files, and epicrisis. Results: Of the 19 patients followed, 15 (78.9%) were female. The mean age was 62.36±12.30 years. Fifteen patients (78.9%) lived in rural areas. Seven patients (36.8%) were involved in animal husbandry. Twelve patients (63.2%) had a history of consuming watercress. The most commonly observed symptoms were loss of appetite, right upper quadrant pain, nausea-vomiting, and night sweats. All patients were treated with triclabendazole without any side effects. Statistically significant differences were found in the levels of eosinophilia, alanine transaminase, gamma-glutamyl transferase, alkaline phosphatase, total bilirubin, and direct bilirubin between the beginning of treatment and 1 month in our patients (p<0.05). One patient was lost due to intervening cardiac problems. Conclusion: Fascioliasis is also present in our region, and a significant history of watercress consumption is noteworthy epidemiologically. Fasciola hepatica should be considered in patients presenting with abdominal pain accompanied by peripheral eosinophilia. Increasing awareness among physicians will contribute to preventing delays in diagnosis and treatment. © 2025 Turkish Society for Parasitology.
Fasciola hepatica Tanısında Klinik ve Laboratuvar İpuçları: Bir Üniversite Hastanesi Deneyimi
Keywords: eosinophilia; Fasciola hepatica; Fascioliasis; watercress